1997
DOI: 10.1021/ja9641416
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of C-2 Glyceryl Radicals:  Indications for a New Mechanism of Lipid Damage

Abstract: Precursors for the selective generation of C-2 glyceryl radicals were synthesized, and the chemical behavior of the corresponding radicals was investigated by ESR spectroscopy, product analysis, and kinetic measurements. It was found that cleavage of the β-C,O bond proceeds rapidly, if a hydroxyl group is present at the radical carbon center. The rate constant for the elimination of a β-acetoxy group from radical 30 was dependent on the solvent (k E = 4 × 105 s-1 in methanol, k E = 2 × 107 s-1 in toluene). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Properties of radical intermediates generated from lipids were studied using various selective and non-selective methods [12]. It has been established [12] that carbon-centered α-hydroxyl-containing radicals formed from lipids are primarily responsible for the fragmentation process. Taking into account the experimentally established facts mentioned above, the DA/Fe 2+ system, which produces • OH radicals according to Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of radical intermediates generated from lipids were studied using various selective and non-selective methods [12]. It has been established [12] that carbon-centered α-hydroxyl-containing radicals formed from lipids are primarily responsible for the fragmentation process. Taking into account the experimentally established facts mentioned above, the DA/Fe 2+ system, which produces • OH radicals according to Fig.…”
Section: Figmentioning
confidence: 99%
“…Previously, we have shown that lipids with structures containing a free hydroxyl group in β-position to the phosphoester, amide or glycoside bonds undergo, along with peroxidation, a free-radical fragmentation process [1,11,12,[14][15][16]. This process occurs in the polar part of the lipid and leads to lipid destruction due to rupture of phosphoester, amide or glycoside bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse-field muon spin rotation (TF-MuSR) method 5 is highly specific for the detection of free radicals which are labelled by a muon, and so radicals formed by addition [Eqn (2)] are the only contributors to the TF-MuSR spectrum; those arising from abstraction are invisible to the muon, which is lost as (non-radical) muonated dihydrogen [Eqn (1)]. …”
Section: Muonium Radiolabelling Techniquementioning
confidence: 99%
“…1 From a recent chemical study, however, has emerged the view that abstraction from the glyceryl unit of a phospholipid, leading to a C-2 glyceryl radical (I), might be of significance. 2 In a lyolipid (II), the resulting glyceryl radical (III) has the structural feature of a hydroxyl group substituting the radical centre, along with two ester moieties: model systems show that the rapid elimination of an acid occurs, leaving an enolate radical (IV); in contrast, acyloxy derivatives (V) are stable to elimination. The significance of lyolipids II is that they are formed at an accelerated rate from normal lipids which have been partially oxidized, and their further oxidation, to radicals of type III, might make a significant contribution to the overall lipid damage, since conversion of III to IV truncates the reconversion, overall, of II to normal lipid.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of flavonols, as well as a number of other flavonoids, is responsible for their useful therapeutic properties. Because of this, it is of considerable interest to study the properties of this class of compounds.Previously [5][6][7][8], it was found that biologically important molecules exposed to γ -radiation and other initiators of free-radical processes can be damaged not only by oxidation but also as a result of fragmentation. In the latter process, the step of degradation of α -hydroxyl-containing radicals plays a key role.…”
mentioning
confidence: 99%